ANALYSIS OF COMPANY PERFORMANCE USING ALTMAN Z-SCORE, GROVER, SPRINGATE, AND ZMIJEWSKI MODELS IN INDICATING THE RISK OF BANKRUPTCY FROM CIGARETTE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2010-2019 - admin, Nindy Belinda B1024171015 (Jurnal Manajemen Update, 2021)
The backgrounds due to impact from Covid-19 pandemic, increase of tobacco excise rates and illegal cigarettes. Research conducted as an anticipatory step in predicting the risk of bankruptcy that might occur using bankruptcy prediction models, First Altman Z-Score, Grover, Springate, and Zmijewski.. The purposes: 1) Obtain discussion results from 4 models to determine company performance in predicting the risk of bankruptcy 2010-2019, 2) Analyze which prediction model has the most accurate results in accordance with actual conditions of cigarette companies listed on IDX to determine the company performance in indicating bankruptcy risk. The research method are One Sample Kolmogorov-Smirnov, Descriptive Statistical test, and Hypothesis test. The results are that there are significant differences between these models and highest level of accuracy achieved by Zmijewski. This model used to do analyze of cigarette companies performance 2010-2019 in general.Keywords: Risk of Bankruptcy, Altman Z-Score, Grover, Springate, and Zmijewski.BIBLIOGRAPHYAdriana. (2012). Analisis Prediksi Kebangkrutan Menggunakan Metode Springate pada Perusahaan Foods and Beverages yang Terdaftar di Bursa Efek Indonesia Periode 2006-2010. Jurnal Repository. Fakultas Ekonomi Universitas Riau.Andriani & Sihombing. (2021). Comparative Analysis of Bankruption Prediction Models in Property and Real Estate Sector Companies Listed on the IDX 2017-2019. European Journal of Business and Management Research, 6(1), 170-173.Almilia & Kristijadi. (2003). Analisis Rasio Keuangan Untuk Memprediksi Kondisi Financial distress Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Jakarta. Jurnal Akuntansi dan Auditing Indonesia, 7 (2).Altman. (1968). Financial ratios, Discriminant Analysis, and The Prediction of Corporate Bankruptcy. Journal of Finance, Vol. 4.Bahar. (2021). Gapero Sebut Peredaran Rokok Ilegal Kian Marak. Accessed from https://www.republika.co.id/berita/qnjwwo416/gapero-sebut-peredaran-rokok-ilegal-kian-marak.Brigham & Daves. (2003). Intermediete Financial Management with Thomson One. United States of America.Bursa Efek Indonesia (BEI) / Indonesia Stock Exchange (IDX). (2018). Detail Profile Perusahaan Tercatat Bentoel International Investama Tbk. Accessed from https://www.idx.co.id/perusahaan-tercatat/profil-perusahaan-tercatat/detail-profile-perusahaan-tercatat/?kodeEmiten=RMBA.Bursa Efek Indonesia (BEI) / Indonesia Stock Exchange (IDX). (2018). Detail Profile Perusahaan Tercatat Gudang Garam Tbk. Accessed from https://www.idx.co.id/perusahaan-tercatat/profil-perusahaan-tercatat/detail-profile-perusahaan-tercatat/?kodeEmiten=GGRM.Bursa Efek Indonesia (BEI) / Indonesia Stock Exchange (IDX). (2018). Detail Profile Perusahaan Tercatat HM Sampoerna Tbk. Accessed from https://www.idx.co.id/perusahaan-tercatat/profil-perusahaan-tercatat/detail-profile-perusahaan-tercatat/?kodeEmiten=HMSP.Bursa Efek Indonesia (BEI) / Indonesia Stock Exchange (IDX). (2018). Detail Profile Perusahaan Tercatat Wismilak Inti Makmur Tbk. Accessed from https://www.idx.co.id/perusahaan-tercatat/profil-perusahaan-tercatat/detail-profile-perusahaan-tercatat/?kodeEmiten=WIIM.CNBC Indonesia. (2020). Ternyata Gelombang PHK sudah terjadi di Pabrik Rokok. Accessed from https://www.cnbcindonesia.com/news/20200515203734-4-158915/ternyata-gelombang-phk-sudah-terjadi-di-pabrik-rokok.Dewi & Ramantha. Prediksi Kebangkrutan menggunakan Model Grover, Zmijewski, & Altman Pada LPD Di Kabupaten Gianyar Tahun 2013-2017. E-Jurnal Akuntansi, 29(3), 1041-1054.Departemen Keuangan Republik Indonesia Badan Pengawas Pasar Modal Proyek Peningkatan Efisiensi Pasar Modal. (2005). Studi Tentang Analisis Laporan Keuangan secara Elektronik.Elviani, Simbolon, Riana, Khairani, Dewi, & Fauzi. (2020). The Accuracy of the Altman, Ohlson, Springate and Zmejewski Models in Bankruptcy Predicting Trade Sector Companies in Indonesia. Budapest International Research and Critics Institute (BIRCI-Journal), 3, 334-47.Endri. (2009). Prediksi Kebangkrutan Bank untuk Menghadapi dan Mengelola Perubahan Lingkungan Bisnis : Analisis Model Altman’s Z-Score. Perbanas Quarterly Review, 2(1).Fauzan & Sutiono. (2017). Perbandingan Model Altman Z-Score, Zmijewski, Springate, dan Grover dalam Memprediksi Kebangkrutan Perusahaan Perbankan (Studi Kasus Pada BEI Tahun 2011–2015). Jurnal Online Insan Akuntan 2.1, 49-60.Fitriya. (2018). Analisis Pengukuran Kinerja Perusahaan dengan Pendekatan Balanced Scorecard pada CV XY (Doctoral dissertation, Universitas Mercu Buana Yogyakarta).Gamayuni & Rika. (2011). Analisis Ketepatan Model Altman sebagai Alat untuk Memprediksi Kebangkrutan (Studi Empiris Pada Perusahaan Manufaktur Di BEI). Jurnal Akuntansi Dan Keuangan 16(2). Fakultas Ekonomi Universitas Lampung.Grover. (2001). Financial Ratios, Discriminant Analysis and The Prediction of Corporate Bankruptcy: A Service Industry Extension of Altman’s Z-Score Model of Bankruptcy Prediction. Working Paper. Southern Finance Assosiation Annual Meeting.Harim. (2018). Metode Pengumpulan Data: Kuantitatif & Kualitatif. Accessed from https://sosiologis.com/metode-pengumpulan-data.Hofer. (1980). Turnaround Strategies. Journal of Business Strategy 1: 19-31.Husein & Pambekti. (2015). Precision of the models of Altman, Springate, Zmijewski, and Grover for predicting the financial distress. Journal of Economics, Business, & Accountancy Ventura, 17(3), 405-416.Husein. (2013). Metode Penelitian untuk Skripsi dan Tesis Bisnis (Edisi 2). Jakarta: Rajawali Pers.Kaloh, Ilat, & Pangerapan. (2018). Analisis Laporan Arus Kas Untuk Menilai Kinerja Keuangan Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia. GOING CONCERN: JURNAL RISET AKUNTANSI, 13(04).Kasmir. (2016). Analisis Laporan Keuangan. Jakarta: PT Raja Grafindo Persada.Kementerian Keuangan Republik Indonesia. (2013). Terapkan UU Pajak dan Retribusi Daerah, 2014 Cukai Rokok Tidak Naik. Accessed from https://www.kemenkeu.go.id/publikasi/berita/terapkan-uu-pajak-dan-retribusi-daerah-2014-cukai-rokok-tidak-naik/.Kementerian Keuangan Republik Indonesia. (2020). Pemerintah tetapkan Kebijakan Tarif Cukai Hasil Tembakau Tahun 2021. Accessed from https://www.kemenkeu.go.id/publikasi/siaran-pers/siaran-pers-pemerintah-tetapkan-kebijakan-tarif-cukai-hasil-tembakau-tahun-2021/.Komarudin. (2019). Analisis Pengaruh Rasio Keuangan Terhadap Kinerja Bank (studi Kasus Pada Perbankan Yang Terdaftar Di BEI Tahun 2011-2015). Indonesian Journal of Strategic Management, 2(1).Luciana. (2004). Analisis Faktor-Faktor yang Mempengaruhi Kondisi Financial Distress Suatu Perusahaan yang Terdaftar di BEJ. JRAI, Vol. 7, No.1.Luciana. (2006). Prediksi Kondisi Financial Distress Perusahaan Go Public dengan Menggunakan Analisis Multinomial Logit. Jurnal Ekonomi dan Bisnis, Vol. XII, No.1.Mulyadi. (2001). Balanced Scorecard: Alat Manajemen Kontemporer untuk Pelipatganda Kinerja Keuangan Perusahaan. Jakarta: Salemba Empat.Munawir. (2010). Analisa Laporan Keuangan, Edisi Keempat, Cetakan Kelima Belas, Yogyakarta: Liberty.Nidhi, Arora, & Saini. (2013). Time Series Model for Bankruptcy Prediction via Adaptive Neuro-Fuzzy Inference System. International Journal of Hybrid Information Technology, 6(2). India.Oktaviandri, Annisa, & Firli. (2017). Analisis Prediksi Kebangkrutan dengan Model Altman, Springate, Ohlson, dan Grover pada Perusahaan di Sektor Pertanian Bursa Efek Indonesia Periode 2011–2015. Majalah Ilmiah UNIKOM.Pradhan & Roil. (2011). Prediction of Z Score for Private Sector Banking Firms. International Referred Research Journal, 2(22). ISSN-0975-3486, RNI: RAJBIL 2009/30097.Primasari & Savitri. (2017). Analisis Altman Z-Score, Grover Score, Springate, dan Zmijewski sebagai Signaling Financial Distress (Studi Empiris Industri Barang-Barang Konsumsi di Indonesia). Accounting and Management Journal 1.1.Riset Kesehatan Dasar. (2018). Jumlah Perokok di Indonesia Tinggi, Ahli Desak Pemerintah Lakukan 5 Hal. Accessed from https://swa.co.id/swa/trends/konsumen-rokok-terus-meningkat-karena-pengaruh-iklan.Shalih & Kusumawati. (2019). Prediction of Financial Distress in Manufacturing Company: A Comparative Analysis of Springate Model and Fulmer Model. Journal of Auditing, Finance, and Forensic Accounting, 7(2), 63-72.Springate. (1978). Predicting the Possibility of Failure in a Canadian Firm. Unpublished MBA Research Project. Simon Fraser University.Sugiyono. (2010). Metode Penelitian Pendidikan. Bandung: AlfabetaSupardi & Mastuti. (2003). Validitas Penggunaan Z-Score Altman untuk Menilai Kebangkrutan pada Perusahaan Perbankan Go Publik di Bursa Efek Jakarta. Kompak, No.1, 68-69.TradeInvest. (2021). Saham Delisting, Kriteria dan Hak Investor Publik. Accessed from https://tradeinvest.id/saham-delisting-kriteria-dan-hak-investor-publik.html.Whitaker. 1999. The Early Stages of Financial Distress. Journal of Economics and Finance, 23: 123-133.Wibowo. (2010). Kinerja tim marketing Dinas Perindustrian Perdagangan & Energi Sumber Daya Mineral (ESDM) Kabupaten Kulon Progo dalam kegiatan pengembangan pasar & distribusi barang/produk.Zmijewski. (1984). Methodological issues related to the estimation of financial distress prediction models. Journal of Accounting Research 22 (Supplement), p. 59-86.